Kenakalan Remaja Putra dan Penanganan Tindak Kekerasan di Panti Putra Islam Giwangan - Pranesa, Dewa Arum; Kurnia, Heri (Academy of Social Science and Global Citizenship Journal, 2021)
An orphanage is a social institution that has the responsibility to provide services, social welfare to orphans, the poor, and abandoned children by carrying out chanting and alleviation, providing physical, mental, social substitute services to foster children, so that the existence of an orphanage institution can help foster children who are lacking in terms of welfare life to be better. This study aims to describe the efforts of orphanages in overcoming juvenile delinquency in the Putra Islam Giwangan orphanage. This research uses qualitative research methods with a descriptive type. Juvenile delinquency at the Putra Islam Giwangan Orphanage, namely fighting, violating, and smoking. some young men commit delinquent acts have their own reasons so that the Giwangan Islamic Boys Orphanage has its own efforts to overcome juvenile delinquency., Efforts made in overcoming juvenile delinquency are coaching, monitoring, supervising and reprimanding and even removing problematic adolescents from the orphanage Juvenile delinquency is a problem that continues to exist and can harm themselves and others. Therefore, supervision and guidance from parents and proper education are needed to prevent negative behavior. Acts of violence are one form of juvenile delinquency that is very detrimental and can be handled by strengthening adolescent mental attitudes, providing education, and guidance from adults.